Prevalence of chronic kidney disease in South Asia: A systematic review - Hasan, Mehedi; Sutradhar, Ipsita; Gupta, Rajat Das; Sarker, Malabika (BMC, 2022)
This article was published in the BMC Nephrology [© The Author(s). 2018 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at: https://doi.org/10.1186/s12884-018-1993-9 The Journal's website is at: https://bmcnephrol.biomedcentral.com/articles/10.1186/s12882-018-1072-5#citeas